Application of Association Analysis to Detect Collusive Behaviour in Public Tenders - Ziarko, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The purpose of this study is to examine the conditions required for the application of association analysis in the identification of the collusive behaviour of contractors in public tenders. It also focuses on determining the values of the confidence and lift measures that will describe the rules specific to a tender cartel. Worldwide research has aimed to develop effective and easy‑to‑use screening tests to identify cartel cases in public procurement. The recent research focuses on price (its distribution, variance, range) and classifiers allowing for detection of contractors whose mode of operation deviates from that commonly observed. This study follows the direction of current research. The main results of the study include the confirmation of the applicability of the method for the detection of colluding entities and the determination of the value of the confidence and lift measures specific to cartel cases. The policymakers, law enforcement agencies, contracting authorities and competitors of the cartels can use the proposed method to eliminate or at least to limit the scale of the problem. The main shortcoming of the application of the results is the inability to apply them to cartels pursuing an avoidance strategy. Further research will be conducted to develop a conceptual application of association analysis to all cartel strategies.